Berpikir Sistem Pada Masifnya Gerakan Feminisme - Nurdyawati, Tika Tazkya (Indonesia Center for Middle East Studies, 2022)
Abstract The equality agenda that is developing massively in the Western world is often transmitted gradually to the Middle East Region. In its early stages, feminism entered into a scientific methodology, paradigm, and concern. Then, feminism spread multidimensionally to the political realm. In the contemporary era, feminism exists as a movement facilitated by digitization. There are two camps as actors who are at war with each other in narratives: 1) Muslim feminists, and 2). Muslim counter-feminist. This article aims to explore the roots of the differences in the premises of the two camps which are equally legitimized by religious references. This article uses a qualitative method with a systems thinking framework attached to the mental model of the Causal Loop Diagram. This research refers to the theory of the narrative’s ability to mobilize public opinion and produce war virtually. The findings of this article find that there are different interpretation schemes between the two camps in religious understanding.